2019
DOI: 10.1371/journal.pone.0215740
|View full text |Cite
|
Sign up to set email alerts
|

Altering the levels of nuclear import factors in early Xenopus laevis embryos affects later development

Abstract: More than just a container for DNA, the nuclear envelope carries out a wide variety of critical and highly regulated cellular functions. One of these functions is nuclear import, and in this study we investigate how altering the levels of nuclear transport factors impacts developmental progression and organismal size. During early Xenopus laevis embryogenesis, the timing of a key developmental event, the midblastula transition (MBT), is sensitive to nuclear import factor levels. How migh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Conventionally, the nuclear-cytoplasmic ratio or karyoplasmic ratio has been considered to be a measure of cellular spatial information (Wilson, 1925; Jorgensen and Tyers, 2004). Previous researches proposed that the nuclear-cytoplasmic ratio dictates cell size-dependent CDC control in budding yeast and MBT triggering in Xenopus embryos (Newport and Kirschner, 1982a; Futcher, 1996) and altered size ratio can affect cell and organismal growth and development, and is associated with disease states (Edens et al, 2013; Jevtić and Levy, 2015; Jevtić et al, 2019). However, quantitative analyses of the allometric size scaling between cell and nucleus have been limited to studies using C. elegans and Xenopus embryos in animal cells (Arata et al, 2014; Jevtić and Levy, 2015).…”
Section: Historical Development Of Quantitative Studies For Cell-divimentioning
confidence: 99%
“…Conventionally, the nuclear-cytoplasmic ratio or karyoplasmic ratio has been considered to be a measure of cellular spatial information (Wilson, 1925; Jorgensen and Tyers, 2004). Previous researches proposed that the nuclear-cytoplasmic ratio dictates cell size-dependent CDC control in budding yeast and MBT triggering in Xenopus embryos (Newport and Kirschner, 1982a; Futcher, 1996) and altered size ratio can affect cell and organismal growth and development, and is associated with disease states (Edens et al, 2013; Jevtić and Levy, 2015; Jevtić et al, 2019). However, quantitative analyses of the allometric size scaling between cell and nucleus have been limited to studies using C. elegans and Xenopus embryos in animal cells (Arata et al, 2014; Jevtić and Levy, 2015).…”
Section: Historical Development Of Quantitative Studies For Cell-divimentioning
confidence: 99%
“…In contrast, Ipo11 in human was expressed in the senescent diploid fibroblasts [24]. Moreover, the Jevtic et al [13] demonstrated that altering the levels of nuclear import factors in early Xenopus laevis embryos affects later development.…”
Section: Discussionmentioning
confidence: 99%
“…Besides this, overexpression of importin-11 can promote bladder cancer (BCa) progression, invasion and migration [12]. Importantly, it has been also reported that altering the levels of nuclear import factors importin α in early Xenopus laevis embryos affects later development [13].…”
Section: Ivyspringmentioning
confidence: 99%
“…Because of CSE1L’s integral function in nuclear transport, it plays an important role in mediating a variety of cellular programs and signal transduction pathways. CSE1L functions as the exporter of importin-α; it has been shown in Xenopus laevis that disruption in levels of importin-α can have striking consequences in the developing embryo [ 38 ]. CSE1L interacts with various members of the Ras/Raf/MEK/ERK pathway, the PI3K pathway, and the cAMP pathway, serving as a hub for various signal transduction pathways [ 11 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%